The Italian executioners: revisiting the role of Italians in the Holocaust. Issue 1 (2nd January 2017) - Levis Sullam, Simon
ABSTRACT: The article revisits the role of Italians in the Holocaust in the light of recent historiography and by applying the category of genocide to the hunting, arrest and deportations of the Jews in Italy in 1943–45, under the German occupation and during the Republic of Salò established by Mussolini. Special attention is given to the ideological context of radical antisemitism, initiated by the introduction of the fascist racial law of 1938 and exacerbated by the Italian civil war, as well as to the role of a variety of ordinary actors, from policemen to volunteers of the fascist party, from bureaucrats to informants.